(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article provides information related to jewelry terms and types of jewelry available in English and Uzbek languages. Jewelry has always been a favorite of women in all countries. The terms related to jewelry in two languages are introduced and compared.